UMP the first public university in the country to use Blockchain Technology for cert validation for its 2,773 graduates - UMP, PNC (2018)
Universiti Malaysia Pahang (UMP) became the first public university in the country to use Blockchain technology for UMP Valid8 - a new application to validate the authenticity of graduation certificates.